Classification of algebras with minimal quadratic growth of identities (São Paulo Journal of Mathematical Sciences, 2007)
The main goal of this paper is to prove that the five algebraswhich were used in [3] to classify (up to PI-equivalence) thealgebras whose sequence of codimensions is bounded by a linear functiongenerate the only five minimal varieties of quadratic growth.